Hubungan Sosial Ekonomi Keluarga dengan Kejadian Stunting pada Balita Usia 24-59 Bulan - Bima Ayu Kenanga Sari; Iwan Ardian; Nutrisia Nu’im Haiya; Intan Rismatul Azizah (STIKes Ibnu Sina Ajibarang, 2025)
Stunting is a body condition in which the stature is short or dwarfed until the body size reaches <-2 elementary school, starting at 1000 HPK the First Day of Birth (HPK). Stunting is caused by socio-economic factors. This study aimed to determine whether there is a socioeconomic relationship with the incidence of stunting in toddlers aged 24-59 months. This study used analytical observations with a case-control approach, with the observation of dependent variables and independent variables. Sixty respondents was 60 people using purposive sampling techniques. The results of data analysis from 60 respondents, the case group of 30 respondents with an average maternal age of 31 years, and the control group of 30 respondents with an average of 30 years of maternal remainder. The average age of toddlers in the case and control groups was 33 and 35 months, respectively, and the majority were women. The mothers’ last education in the case group was dominated by low (73.3%), and the control group had a high majority (73.3%). The socio-economic level in the majority of cases was bad at 70% and the control group was mostly in the good category at least 56.7%. The results of the chi-square test showed a relationship between socioeconomic status and stunting incidence in toddlers aged 24-59 months in the working area of the Gajah 1 Health Center.